A Pacific free trade area - Kiyoshi Kojima (Intereconomics, 1968)
Great Britain's desire to join the Common Market has given a fresh impetus to the plans of a Pacific-Asiatic free trade area. Members of PAFTA are to be Japan, the United States, Canada, Australia, and New Zealand. By means of an economic integration of these nations, particularly Japan is interested in stabilising its position in the world economy and not to stand completely outside regional unions. Already last year, INTERECONOMICS published a critical comment to the PAFTA plans written by the Australian professor, H. W. Arndt. In view of the manifold problems and the economic disadvantages to be anticipated, he declared against an Australian participation in this project. In the following article, Professor Kojima, the initiator of the Pacific integration plans, takes a different point of view.
Keywords: 330; Integration